EVALUASI KUALITAS HIDUP PASIEN DIABETES MELITUS TIPE 2 YANG DITERAPI RAWAT JALAN DENGAN ANTI DIABETIK ORAL DI RSUP Dr. SARDJITO - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Type 2 Diabetes Mellitus is a chronic disease which can't be healed totally. Therefore type 2 DM will affect the Health Related Quality of Life (HRQOL). The purpose of this study was to determinate the QOL of type 2 DM patients based on patient's characteristics, drug groups, and therapy pattern (single versus combination therapy). This study was conducted in RSUP Dr. Sardjito Yogyakarta. This study is an analytical research with cross sectional design. Data collection was done by interview and review of patient's medical records. Research's subjects are ambulatory patient with type 2 DM who are threated with oral antidiabetic(s) and willing to fill the questionnaire. Total 227 total patients were included in this study. Quality of life was measured by Diabetes Quality of We Oinical Trial Questionnaire (DQLCfQ). The analysis showed that gender, age, duration of DM, educational level. marital status and occupation affect the QOL. Patient taking metforrnin had 67.9 score, 67.7 for patient with acarbose therapy and patient taking sulfonylurea 67.6 score. Those differences were not signifIcant (ANOVA test,. P = 0.298). Patients taking single antidiabetic agent had 70.6, whereas those taking combination therapy had 67.6 score. Independent sample t-test showed that those score have significant difference (p = 0.002).Linear regressionanalysis with enter method showed that QOL'sdiffer-ence between single and combination therapy groups did affected by patient's characteristics (p=0.049).